Influence of Underconsolidating Soil on Effective Stress Path in a Deep Excavation Case - Albert Sebastian; Lim, Aswin (Indonesian Geotechnical Journal, 2025)
This study investigates the influence and impact of clay soil that is presumed to be undergoing consolidation process on an unbraced shallow excavation system. The excavation geometry spans up to 160 meters with a maximum depth of 5.25 meters. A concrete sheet pile wall was installed at the front side of the excavation, supported by additional tie beams connected to square precast piles behind the wall. Based on soil investigation data, residual excess pore water pressures were identified within the underconsolidating clay layer at depths between 3 to 12 meters. These residual pore pressures contribute additional loading to the retaining wall system. A back analysis was conducted to obtain appropriate soil parameters to be used for PLAXIS 2D modelling. The finite element analysis results were compared with inclinometer data to validate the back analysis. Modeling of the underconsolidating condition was performed by manually inputting the pore water pressure into the initial condition. Results show that under underconsolidating conditions, the maximum wall deflection reached 190 mm, whereas under hydrostatic conditions, it was only 100 mm. Additionally, a parametric study was carried out to examine the relationship between the degree of consolidation and wall deflection. The findings indicate that a higher degree of consolidation leads to reduced wall deflection. To investigate the stress changes on the wall due to underconsolidating soil, a stress path analysis was performed to understand the stress history around the excavation. It was found that in underconsolidating conditions, the average effective stress tends to be lower and the deviatoric stress higher, resulting in a stress path that is closer to the failure line.